Non-Causal Effects of Asthma on COVID-19 Susceptibility and Severity - Qiu, Li-Juan; Yin, Kang-Jia; Pan, Gui-Xia; Ni, Jing; Wang, Bin (Frontiers in Genetics, 2022)
Purpose: Asthma account for the most common non-infectious respiratory pathologies. Conflicting preliminary findings have reported that asthma likely associated with risk of COVID-19, whereas, it remains unclear whether there is a casual relationship of asthma with susceptibility to SARS-CoV-2 infection or COVID-19 severity. Methods: Instrumental variables (IVs) for asthma and moderate-to-severe asthma were obtained from publicly available summary statistics from the largest and most recent genome-wide association studies, including 394 283 and 57 695 participants of European descent, respectively. The corresponding data for COVID-19 were available from the COVID-19 Host Genetics Initiative GWAS of up to 1 683 768 individuals of European ancestry were used for COVID-19 susceptibility, hospitalization and severe-disease outcome. Causality was inferred between correlated traits by Mendelian Randomization analyses. Primary MR estimates were calculated with inverse-variance weighted method, and several alternate methods and multiple sensitivity analyses were also performed. Results: Our MR suggested that asthma was not associated with an increase in COVID-19 susceptibility, hospitalization or severe disease, with odds ratios (OR) per standard deviation increment of 1.00 (95% CI: 0.97-1.04), 1.07 (95% CI: 0.96-1.19), and 0.94 (95% CI: 0.85-1.05), respectively. Furthermore, using genetic variants for moderate-to-severe asthma, the result was similar for susceptibility (OR: 0.97, 95% CI: 0.90-1.01), hospitalization (OR: 0.96, 95% CI: 0.86-1.08), and severity (OR: 0.88, 95% CI: 0.79-0.98). The association of asthma with COVID-19 was overall robust to sensitivity analyses. Conclusion: Genetically predicted asthma was not associated with susceptibility to, or severity of, COVID-19 disease, suggesting that asthma is unlikely to be a causal factor in the development of COVID-19.